2003
DOI: 10.1161/01.cir.0000091234.45664.62
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Reduction of Aldosterone in Response to the Angiotensin Receptor Blocker Valsartan in Patients With Chronic Heart Failure

Abstract: MD; for the Valsartan Heart Failure Trial InvestigatorsBackground-Aldosterone has been implicated in the progression of heart failure. The Valsartan Heart Failure Trial (Val-HeFT) provided the first opportunity to examine the long-term effects of an angiotensin receptor blocker on plasma aldosterone levels in patients with NYHA class II through IV heart failure. Methods and Results-Plasma aldosterone was measured by radioimmunoassay in core laboratories at baseline and during follow-up in patients assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 32 publications
3
47
0
3
Order By: Relevance
“…A previous report has also shown that the cardiac, and not the adrenal, steroidogenic system is activated in MI rats. 9 These data are consistent with results from human clinical studies 25,26 showing that plasma aldosterone concen- trations were normal or decreased 1 month after the onset of renin-angiotensin system blockade and that the aldosterone escape phenomenon is generally induced only after long-term (several months or longer) treatment. Therefore, it is possible that different molecular mechanisms underlie the aldosterone escape phenomenon in adrenal glands and Ang II-independent aldosterone synthesis in post-MI hearts.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A previous report has also shown that the cardiac, and not the adrenal, steroidogenic system is activated in MI rats. 9 These data are consistent with results from human clinical studies 25,26 showing that plasma aldosterone concen- trations were normal or decreased 1 month after the onset of renin-angiotensin system blockade and that the aldosterone escape phenomenon is generally induced only after long-term (several months or longer) treatment. Therefore, it is possible that different molecular mechanisms underlie the aldosterone escape phenomenon in adrenal glands and Ang II-independent aldosterone synthesis in post-MI hearts.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, our results also show that a relatively low dose (20 mg/kg per day) of spironolactone, which does not affect hemodynamics, can significantly attenuate LV remodeling. Recently, Cohn et al 26 reported sustained reduction of the plasma aldosterone level after renin-angiotensin system blockade using valsartan, but such reduction was independent of the clinical outcome in CHF patients, suggesting the significance of the aldosterone level in the myocardium rather than the level in plasma. Taken together, these previous data and our present results suggest that locally produced aldosterone in post-MI hearts could play a primary role in the pathogenesis of LV remodeling in an autocrine or paracrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aldosterone production in the vasculature may have influenced the results of our experiments. Recent studies have demonstrated that plasma aldosterone levels tend to increase with the duration of ACE inhibitor treatment (25,26), whereas an AT1 receptor antagonist showed no evidence of aldosterone escape (27), suggesting that aldosterone escape may have made a greater contribution to the SMC phenotypic change in intramyocardial arteries in SHR following enalapril treatment than following FK-739 treatment.…”
Section: Fig 3 Representative Immunoblot Staining For Sm-mhc Isoformentioning
confidence: 99%
“…Как уже отмечалось выше, значительную роль в патофизиологии сердечной не-достаточности играет повышение уровня альдостеро-на, а также кортизола [24,25], поэтому у таких пациентов увеличено количество рецепторов минералокорти-коидов в ткани миокарда [26,27]. Несмотря на терапию ингибиторами АПФ/АРА и бета-адреноблокаторами, у пациентов даже с «мягкими» проявлениями сердеч-ной недостаточности чаще всего наблюдаются повы-шенные уровни альдостерона и кортизола крови [28][29][30][31][32][33]. Ни ингибиторы АПФ/АРА, ни бета-адреноблока-торы не оказывают блокирующего действия на эти ре-цепторы.…”
Section: эплеренон и сердечная недостаточностьunclassified